Secondary aluminium, iron and silica phases across a volcanic soil climosequence, Galápagos Islands. (15th May 2019) - Taboada, Teresa; Ferro‐Vázquez, Cruz; Stoops, Georges; Martínez‐Cortizas, Antonio; Rodríguez‐Flores, Ruth; Rodríguez‐Lado, Luis
Abstract : We applied selective dissolution extractions (Na‐pyrophosphate, acid oxalate, cold NaOH and citrate‐dithionite) to study Al, Fe and Si fractionation in 38 volcanic pedons located on the windward slopes of Santa Cruz (Galápagos Islands) that form a climosequence. The aim was to evaluate the distribution of secondary Fe, Al and Si phases in relation to environmental variables. Two main trends were observed: a geographical pattern in relation to altitude and a vertical differentiation within soil profiles. Soils from the drier coastal area had the smallest amounts of secondary Al, Fe and Si, whereas values were larger in soils at higher altitude, under a more humid climate. Organo–metallic complexes dominate the organic‐rich topsoils in these wetter areas as a result of larger availability of free Al, more humified organic matter with a greater capacity for metal adsorption and larger organic matter contributions from vegetation. This has led to increased accumulation of organic carbon in soils at higher altitudes. At lower elevations, inorganic secondary materials are more frequent, with short‐range‐order minerals prevailing in topsoils, whereas crystalline minerals dominate subsoils. Crystalline minerals are also frequent in some soils at higher altitudes in relation to acid pH. Vertical differentiation within the soil profile is also responsive to altitude: differences between topsoils and subsoils are generally more marked in soils at higher locations, thus wetter areas. A greater degree of weathering seems to be the main factor controlling both altitudinal trends and horizonation through its effect on pH, organic matter content and humification, ultimately controlled by climatic variation. Highlights: We analysed soils developed on volcanic material along the windward slope of Santa Cruz Island. Organo–metallic complexes are abundant in acidic, organic‐rich epipedons at higher elevation. Short‐range‐order minerals are more abundant in non‐acidic subsoils and tend to increase with altitude Crystalline minerals predominate at lower elevation and in acidic subsoils at higher altitude.